The Effectiveness of Spiritual Emotional Breathing Towards Respiratory Function and Immune Response of Tuberculosis Patients - Kusnanto Kusnanto; Joni Haryanto; Tintin Sukartini; Elida Ulfiana; Made Mahaguna Putra (Universitas Airlangga, 2018)
Introduction: Tuberculosis is one cause of infectious death worldwide. In relation to the healing of pulmonary tuberculosis in Indonesia, there are still certain areas where the cure rate is still low. This study aims to identify the effect of spiritual emotional breathing (SEB) on the quality of respiratory function and the modulation of immune response in tuberculosis patients.Methods: The study used a quasi-experimental design with two groups of pre-post-test design. The population was 34 patients with tuberculosis in East Perak’s primary health care. The independent variable was SEB (spiritual emotional breathing). The dependent variables were peak expiratory flow rate (PEFR), pulse, oxygen saturation, breath frequency, breath sound, stiffness complaints, human IL-2, human cortisol, IgG.Results: The results showed that there was a significant difference in PEFR, pulse, oxygen saturation, respiratory rate, respiratory sound, stiffness, human IL-2, human cortisol, IgG.Conclusion: SEB can improve the quality of respiratory function and the modulation of immune response in tuberculosis patients. The emotional spiritual approach is part of the science of energy psychology that aims to turn the negative energy in a person into positive energy that can help the healing process. This therapy is performed as a complementary therapy for TB patients to improve their quality of life and the control of symptoms